A retrospective (2004-2013) and prospective (2014-2015) study of new born with special reference to anorectal malformations over a period of 10 years at a tertiary care centre - Sharma, Shashi Shankar; Ansari, Arif Ahmad; Shukla, Kartikeya; Laddha, Ashok; Lahoti, Brijesh (International Journal of Research in Medical Sciences, 2016)
Background:A surgical audit of neonates with anorectal malformation in advanced tertiary neonatal care unit. Methods: A retrospective (2004-2013) and prospective (2014-2015) audit of medical records of newborn with GIT disorders admitted in a tertiary care center of central India. The trends analyzed for the duration based on gender, region and birth weight and data base was generated depicting the burden of disease in the region. The data base for the prospective study was also compared with a tertiary center from Nigeria. Results:Total 3309 admission included 73.56% (2438) patients of GIT diseases. Congenital anomalies were the most common cause in each category, major part being anorectal malformation (727) and trachea-esophageal fistula (730). Out of 727 admissions, 651 neonates were operated & total 1194 deaths recorded during this audit year 2004 to July 2015. Majority of new born admitted with were low birth weight male from rural skirts of this region. 509 have associated anomalies and 218 isolated ARM. Conclusions:There is significant increase in admissions in last decade with triple fold increase in GIT disorder and twice rate in anorectal malformation substantially increasing onwards. The quality of management has to continue further to achieve parity with international standards, as there is lack of antenatal screening and details of any antenatal checkup are scarce, for congenital anomalies at primary level. Early recognition, risk stratification of the baby and timely referral to higher pediatric surgery units is the way forward.